Microbiological Assessment of Roasted Dried Periwinkle (Tympanotonus Fuscatus) Sold in Yenagoa Bayelsa State - Obhioze Augustine Akpoka (International Journal of Applied Biology, 2020)
The microbial load of dried periwinkle(tympanotonus fuscatus) sold in Opolo market, Swali market and Kpansia market in Yenagoa were assessed and the microorganisms isolated were identified. Three samples were bought from Opolo market, Swali market and Kpansia market respectively were assessed. Total bacterial populations of the samples from Opolo market range from 37×10-5- 12×10-5 cfu/g, Swali range from 49×10-5 - 29×10-5 cfu/g, while Kpansia market range from 38×10-5- 18×10-5 cfu/g. For fungi population, Opolo market range from 6×10-5 - 1×10-5 cfu/g, Swali market range from 9×10-5- 3×10-5 cfu/g, while Kpansia market range from 7×10-5 - 2×10-5cfu/g. The Samonella/Shigella counts from Swali market range from 13×10-5- 2×10-5 cfu/g, kpansia market range from 12×10-5- 3×10-5 cfu/g, while Opolo market range from 11×10-5-1×10-5 cfu/g. The coliform counts from Swali market range from 30×10-5 - 12×10-5 cfu/g, Kpansia market range from 28×10-5 - 10×10-5  cfu/g, while Opolo market range from 25×10-5- 11×10-5 cfu/g. For fungi population, Opolo market range from 6×10-5- 1×10-5 cfu/g, Swali market range from 9×10-5-3×10-5 cfu/g, while Kpansia market range from 7×10-5 - 2×10-5 cfu/g.The bacterial isolates belonged to six genera identified as: Klebsiella, Salmonella, Escherichia coli, Shigella, Staphylococcus and Bacillus. The percentage (%) occurrences of the bacterial isolates were: Bacillus sp. (28.5%), Staphylococcus aureus (25%), Shigella sp. (21.4%), Escherichia coli (17.9%), Salmonella sp. (3.6%) and Klebsiella sp. (3.6%). Four (4) fungal isolates were obtained from the dried periwinkle samples and two belonged to the genus Aspergillus, while the other two isolates belong to the genera Penicillium and Mucor. The percentage (%) occurrence of the fungal isolates were: Mucor (41.6%), Aspergillus flavus (25%), Aspergillus niger (16.7%) and Penicillium (16.7%). There was no significant difference in total viable count between one market and another at 5% level of significance (p0.05). Also, there was no significant difference in total viable count between one seller and other sellers. The occurrence of Bacillus, Shigella, Staphylococcus, Klebsiella, Escherichia coli, Salmonella, Aspergillus, and Mucor species are pinpointing the high pathogenicity and health hazard in consuming the dried periwinkle. Due to the soaring demand of this sea food (periwinkle) and the health hazard associated with microorganisms isolated from them as revealed in this study, additional concentration should be paid to safety through proper storage and handling processes and it is important that periwinkle should be properly cooked before consumption.